Relationship between 21st Century Skills and Socialization among Students at Undergraduate Level in Public Universities of Lahore - Shahzadi, Iqra; Ullah, Shamim; Bibi, Iqra (Annals of Human and Social Sciences, 2024)
This study explored the relationship between 21st-century skills and socialization among undergraduate students in public universities in Lahore. The main objectives were to determine skill levels and socialization patterns. The sample consisted of 320 participants (230 females and 90 males) selected through multistage stratified random sampling. Data were collected using a descriptive, quantitative design with a correlation method. Two main variables were examined: 21st-century skills and student socialization. A questionnaire, adapted from Mehmet İnan (2015), assessed attitudes towards socialization, including communication, collaboration, creativity, critical thinking, and media literacy. The 50-item scale had a Cronbach's alpha of .816. The study highlights that while there are some significant differences in skill levels between students of different universities, gender does not play a significant role in most skill areas. The findings suggest that educational institutions need to focus on creating balanced and inclusive learning environments that cater to the development of a wide range of skills. Implementing the recommended strategies can help in achieving this goal, ensuring that all students, regardless of gender or university affiliation, have the opportunity to develop the essential skills needed for personal and professional success.